2017
DOI: 10.1016/j.celrep.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Pathway for Regulation of CCL2 Expression by an mTORC1-FOXK1 Axis Promotes Recruitment of Tumor-Associated Macrophages

Abstract: C-C chemokine ligand 2 (CCL2) plays pivotal roles in tumor formation, progression, and metastasis. Although CCL2 expression has been found to be dependent on the nuclear factor (NF)-κB signaling pathway, the regulation of CCL2 production in tumor cells has remained unclear. We have identified a noncanonical pathway for regulation of CCL2 production that is mediated by mammalian target of rapamycin complex 1 (mTORC1) but independent of NF-κB. Multiple phosphoproteomics approaches identified the transcription fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 45 publications
8
83
0
Order By: Relevance
“…Instances of variable dysregulation could be due to compensatory mechanisms or interdependence of specific mediators, as in the case of TNF and Egr1 37 . The data also demonstrate that not all signaling is impaired by TAK1‐inhibition (e.g., CCL2), suggesting predominant/compensatory control by signaling cascades with TAK1‐independent aspects such as the mTOR/FOXK1 axis 65 . TAK1 has long been known to be an important player in various signaling‐induced outcomes, including inflammation driven by other cell types, and in other disease models.…”
Section: Discussionmentioning
confidence: 77%
“…Instances of variable dysregulation could be due to compensatory mechanisms or interdependence of specific mediators, as in the case of TNF and Egr1 37 . The data also demonstrate that not all signaling is impaired by TAK1‐inhibition (e.g., CCL2), suggesting predominant/compensatory control by signaling cascades with TAK1‐independent aspects such as the mTOR/FOXK1 axis 65 . TAK1 has long been known to be an important player in various signaling‐induced outcomes, including inflammation driven by other cell types, and in other disease models.…”
Section: Discussionmentioning
confidence: 77%
“…The mTORC1-FOXK1 pathway senses amino acid changes in CM and regulates CCL2 expression independent of NF-κB signaling by dephosphorylating the transcription factor FOXK1. 45 We tested the activation of the mTORC1-FOXK1 pathway in MΦ, MS, and MR and found that activation of the mTORC1-FOXK1 pathway was consistent with the secretion trend of CCL2 ( Figure 3C). These results suggest that TNFα and amino acid metabolism in CM activate the NF-κB and mTORC1-FOXK1 pathways of TAM promoting the secretion of CCL2.…”
Section: Tumor Necrosis Factor Alpha and Amino Acid Metabolism In Cmentioning
confidence: 74%
“…Although mTORC1 induces dephosphorylation of FOXK1 via PP2A, the signaling cascade has not been fully uncovered (Nakatsumi et al, 2017). In the present study, we identified B56 as the B subunit of PP2A that is required for the FOXK1 dephosphorylation.…”
Section: Discussionmentioning
confidence: 65%
“…We previously showed that mTORC1 induces PP2Amediated multiple dephosphorylation of the transcription factor forkhead box K1 (FOXK1) (Nakatsumi, Matsumoto, & Nakayama, 2017). The dephosphorylated FOXK1 transactivates C-C chemokine ligand 2 (CCL2), a proinflammatory chemokine that promotes the accumulation of monocytesmacrophages at inflammatory sites (Deshmane, Kremlev, Amini, & Sawaya, 2009;Matsushima, Larsen, DuBois, & Oppenheim, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation